2005
DOI: 10.1016/j.virol.2004.11.032
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1 Tat protein induces an intracellular calcium increase in human monocytes that requires DHP receptors: involvement in TNF-alpha production

Abstract: HIV-1 Tat protein, acting at the cell membrane, stimulates the production by human monocytes of TNF-alpha, a cytokine implicated in both HIV-1 replication and pathogenesis. Here, we analyze, in primary human monocytes, the mechanisms involved in Tat-stimulated calcium mobilization and its relationship with TNF-alpha production. We show that the Tat protein induces a calcium signal by mobilizing calcium from extracellular stores. This calcium signal is totally blocked when cells are stimulated in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 55 publications
3
23
0
Order By: Relevance
“…When challenged with 100 nM Tat, [Ca 2ϩ ] i levels rose to ϳ150 nM in day 2 OLs and ϳ230 nM in day 7 OLs, and these increased [Ca 2ϩ ] i levels were maintained during a 20 min experimental period (Fig. 6 B, D-F CaMKII␤ is a molecule central to OL intracellular Ca 2ϩ signaling pathways (Derkach et al, 1999;Bayer and Schulman, 2001;Hudmon and Schulman, 2002) and has been reported to be important in maturation and myelination (Waggener et al, 2013). We investigated whether CaMKII␤ was activated as a consequence of the Tat-induced [Ca 2ϩ ] i increase.…”
Section: Tat Induces Ca 2؉ Influx and Camkii␤ Activation In Both Matumentioning
confidence: 96%
See 2 more Smart Citations
“…When challenged with 100 nM Tat, [Ca 2ϩ ] i levels rose to ϳ150 nM in day 2 OLs and ϳ230 nM in day 7 OLs, and these increased [Ca 2ϩ ] i levels were maintained during a 20 min experimental period (Fig. 6 B, D-F CaMKII␤ is a molecule central to OL intracellular Ca 2ϩ signaling pathways (Derkach et al, 1999;Bayer and Schulman, 2001;Hudmon and Schulman, 2002) and has been reported to be important in maturation and myelination (Waggener et al, 2013). We investigated whether CaMKII␤ was activated as a consequence of the Tat-induced [Ca 2ϩ ] i increase.…”
Section: Tat Induces Ca 2؉ Influx and Camkii␤ Activation In Both Matumentioning
confidence: 96%
“…sence of viral replication, and has been shown to be at high titers in the CSF of cART-controlled patients (Johnson et al, 2013). Multiple cellular abnormalities have been reported in Tat transgenic mice, including reactive astrogliosis and microgliosis (Bruce-Keller et al, 2008), elevated caspase-3 activation in OLs , and synaptodendritic injury (Kim et al, 2003;Fitting et al, 2014), which coincides with deficits in behavior, including learning and memory (Carey et al, 2012;Fitting et al, 2013), and cognitive/motor impairments (Hahn et al, 2015). Most studies suggest Tat-induced inflammation as the predominant cause of CNS injury.…”
Section: Effects Of Tat In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Different domains of Tat can interact with specific membrane receptors, including the CD26 receptor (58), the CXCR4 chemokine receptor (46), the L-type calcium channel (59), integrin ␣v␤3 and ␣5␤1 of DCs (60), membrane lipids (55), and the Flk-1/KDR receptor (61). In addition to these potential Tat receptors, we have recently demonstrated that Tat protein is able to recruit the Tolllike receptor 4 (TLR4) pathway, following its interaction with high affinity with TLR4-MD2 complex, to activate the production of proinflammatory tumor necrosis factor alpha (TNF-␣) and antiinflammatory interleukin 10 (IL-10) cytokines (62).…”
mentioning
confidence: 99%
“…39) However, Xavier et al reported that calcium ions are mobilized from the extracellular environment to enter the cytoplasm through L-type calcium channels and that such mobilization promotes TNF-a production in human PBMCs. 40) A transient rise of [Ca 2ϩ ] i induces persistent activation of NF-kB, 41) which results in the production of TNF-a and MCP-1. An increase of [Ca 2ϩ ] i also causes the activation of Akt, 35) which enhances cytokine production via NF-kB activation, while activated Akt implies the rise of [Ca 2ϩ ] i through the activation of L-type calcium channels.…”
Section: Fig 2 Inhibition Of Cytokine Productionmentioning
confidence: 99%